PELATIHAN DOKTER KECIL TENTANG KESEHATAN TELINGA DENGAN MEDIA KALENDER BALIK PADA SISWA SEKOLAH DASAR - Rahayu, Made Lely; Rinika Pranitasari, Ni Putu Oktaviani; Raditya, I Gede Wahyu Adi; pradhipta, putu yupindra; Danastri, I Gusti Ayu Mahaprani (Buletin Udayana Mengabdi, 2024)
Ear health is an important aspect of overall health. The ear is not only a hearing organ, but also has a role in keeping the body in balance. Serumen plays an important role in keeping the ear clean and protecting it from dust, dirt and infection. Hearing loss can affect children's speech comprehension, language and social development. Increased awareness and prevention of hearing loss in children needs to be carried out continuously. The Department of ENT-BKL FK UNUD conducts community service activities with a small doctor training program to prevent hearing loss due to earwax in children.. Keywords: Ears, Serumen, Hearing Loss, Little Doctor, Community Service.